Lifelong Access to Career Guidance - a Key to Lifelong Learning : Interview with Professor Tony Watts - Watts, Tony [Interviewter]; Jäger, Christiane [Interviewer] (My University, 2016)
"The level of expectations raised in EU policy papers on lifelong guidance is high when requiring that guidance should enable citizens to identify their capacities, competences and interests, to make educational, training and occupational decisions and to manage their individual life paths at any time in their lives. How can such an ambitious concept be implemented and embedded into the educational and employment system? Professor Tony Watts, dealing with career guidance for over 30 years and gaining insights on the worldwide development of guidance due to his work as international consultant will give us answers to this question and related issues." (BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Lebenslanges Lernen; Beratung; Bildungsberatung